Effectiveness of TikTok Video-Based Nutrition Education in Improving Dietary Knowledge: A Pre-Experimental Study Among Adolescent Girls in Banggai, Indonesia - Herawati Herawati; Veny Hadju; Sukri Palutturi; Muhammad Isyraqi Ghazian; Maria Kanan; Dwi Wahyu Balebu; Lisa Handayani; Sandy N. Sakati; Ulin Na’ma Saputra (Journal of Health and Nutrition Research, 2026)
Adolescent girls undergo rapid physical and psychosocial changes, resulting in increased nutritional needs and a higher susceptibility to iron-deficiency anemia, especially at the onset of menstruation. This makes them an important target group for nutrition interventions. This study aimed to assess the effectiveness of TikTok-based nutrition education videos in enhancing adolescent girls' knowledge of diverse diets and balanced nutrition. A pretest-posttest design was used, with no control group, and involved 146 students aged 12-18 years from two schools in Moilong District, Banggai Regency, Central Sulawesi, Indonesia. Participants attended four sessions over eight weeks, each featuring two TikTok videos on topics such as balanced nutrition, anemia prevention, physical activity, healthy eating habits, and menstrual hygiene management. Nutrition knowledge was assessed before and after the intervention using a structured questionnaire, and the data were analyzed using paired t-tests. The results showed a statistically significant increase in nutrition knowledge (p < 0.05). At SMAN 1 Moilong, knowledge scores improved from 40-85 to 70-90, while at SMPN 4 Toili, scores increased from 40-75 to 70-100. These findings demonstrate that short, contextually relevant TikTok videos are effective in improving adolescent girls' nutrition knowledge. Schools and health services are encouraged to incorporate TikTok-based content into routine nutrition education programs, complemented by digital literacy support.